USING KAHOOT AS EVALUATION MEDIA SCIENCE LEARNING DURING THE PANDEMIC COVID-19 - Puspa Cantika Riana; Kiki Fatmawati; Ahmad Maghfur; Nurpaizah (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
In this era of the Covid-19 pandemic, learning activities have to be carried out from home. Due to network limitations, student interest in doing assignments is low. Thus, teachers tend to ignore the assessment of learning outcomes during the pandemic. Whereas assessing learning outcomes is very important to do, one of which is a daily test which aims to determine the extent to which students understand the lesson. For this reason, it is necessary to present an innovation in the field of education, especially in the evaluation process. Especially with the current situation where the level of technology is already high and on average each student already has a Smartphone. Therefore, there is a need for learning innovation by utilizing technology, namely the Kahoot application. This study aims to determine student learning outcomes in science subjects using Kahoot media. The research method used is applied research, namely by implementing the Kahoot application in science learning for online assessment. The data collection method used is a questionnaire. Quantitative data collection was obtained by closed questions. Questionnaires were given after students did daily tests using Kahoot which was oriented to science learning. The daily test consists of 10 multiple choice questions. Based on the results of daily tests, 15 students answered 9 questions correctly, as many as 3 students, 8 questions correctly as many as 6 students, 7 questions correctly as many as 4 students and 2 students answered 6 questions correctly. Based on the students' perception, the use of Kahoot is very interesting and motivates them to remember what they have learned.